2010
DOI: 10.1016/j.jclinepi.2009.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A most stubborn bias: no adjustment method fully resolves confounding by indication in observational studies

Abstract: Objective-To evaluate the effectiveness of methods that control for confounding by indication, we compared breast cancer recurrence rates among women receiving adjuvant chemotherapy versus those who did not.Study Design and Setting-In a medical record review-based study of breast cancer treatment in older women (n=1798) diagnosed 1990-1994, our crude analysis suggested adjuvant Publisher's Disclaimer: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
271
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(281 citation statements)
references
References 42 publications
1
271
0
2
Order By: Relevance
“…For example, there have been many claims about the benefits of various vitamin supplements based on observational studies 128,129 that have been reliably refuted by large-scale randomized trials. [130][131][132] Similarly, when compared with the results from randomized trials of the effects of treatments for several different cancers, observational studies have generated improbable results despite controlling for comorbidity, extent of disease and many other characteristics that were recorded in detailed databases [133][134][135] (as is also the case for reported associations of statins with lower rates of cancer 90,[136][137][138] ). These findings are consistent with empirical studies in which biases in observational studies were shown to be large enough to conclude falsely that treatment produced benefit or harm, with none of a range of statistical strategies (such as regression analysis or propensity matching) capable of adjusting adequately or predictably for bias.…”
Section: Biases Due To Differences In Underlying Risks Of Health Outcmentioning
confidence: 99%
“…For example, there have been many claims about the benefits of various vitamin supplements based on observational studies 128,129 that have been reliably refuted by large-scale randomized trials. [130][131][132] Similarly, when compared with the results from randomized trials of the effects of treatments for several different cancers, observational studies have generated improbable results despite controlling for comorbidity, extent of disease and many other characteristics that were recorded in detailed databases [133][134][135] (as is also the case for reported associations of statins with lower rates of cancer 90,[136][137][138] ). These findings are consistent with empirical studies in which biases in observational studies were shown to be large enough to conclude falsely that treatment produced benefit or harm, with none of a range of statistical strategies (such as regression analysis or propensity matching) capable of adjusting adequately or predictably for bias.…”
Section: Biases Due To Differences In Underlying Risks Of Health Outcmentioning
confidence: 99%
“…The results of such retrospective design can be significantly influenced by differences in patient characteristics related to prognosis that drive the decision of whether to use RIC or CIC. 33 Patients with co-morbidities could have been assigned to RIC regimens, whereas those with higher-risk disease were assigned to the CIC regimens according to the discretion of treating physicians. This should have resulted in a higher TRM in the RIC group unless the RIC regimens truly lowered it, which is likely given the higher co-morbidity score difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Also in case of these outcome variables, IV analysis has been applied with two-stage method. In that case, the second-stage model could be a Cox proportional hazards model [78][79][80]. However, Brookhart et al [3] stated that this approach for IV analysis is not motivated by a theoretical model and, therefore, parameters that are obtained from this approach may not be causally interpretable.…”
Section: Other Estimation Methodsmentioning
confidence: 99%
“…However, Brookhart et al [3] stated that this approach for IV analysis is not motivated by a theoretical model and, therefore, parameters that are obtained from this approach may not be causally interpretable. Examples of this approach are a study of the effect of rosiglitazone on (time to) cardiovascular hospitalization and all-cause mortality using facility-prescribing patterns as an IV [78], and a study of the effect of adjuvant chemotherapy on (time to) breast cancer recurrence using physician preference as an IV [79].…”
Section: Other Estimation Methodsmentioning
confidence: 99%